The Centenary of International Committee of Historical Sciences - Filipowska , Karolina (Studia Historiae Oeconomicae, 2025)
On May 15, 1926 the International Committee of Historical Sciences (ICHS or Comité international des sciences historiques – CISH) was founded in Geneva as a non-governmental organization intended to bring together historians from all over the world. The 100th anniversary of this event is approaching.